Air quality modelling as a supplementary assessment method in the framework of the European Air Quality Directive. (1st January 2014) - Ribeiro, I.; Monteiro, A.; Fernandes, A.P.; Monteiro, A.C.; Lopes, M.; Borrego, C.; Miranda, A.I.
According to the European Air Quality (AQ) Directive, member states must annually report their AQ to the European Commission (EC). This report can be based on modelling data if the concentration levels do not exceed the established lower assessment thresholds (LAT), or on combined data from modelling and monitoring systems (supplementary assessment methods) if concentrations levels are below the upper assessment threshold (UAT). This work presents and applies a methodology that combines air pollutant concentration values from monitored data and from a numerical modelling system to deliver AQ information for Portugal in 2010. This methodology produces improved information, especially for areas where the amount of fixed monitoring stations is sparse or non-existent, allowing obtaining a better and broader overview of the AQ in Portugal to support AQ reporting to the European Commission.